Direct Stereoselective Method Development and Validation of Elagolix on Zwitterionic Chiral Stationary Phase by High-Pressure Liquid Chromatography (International Journal of Pharmaceutical Sciences and Drug Research, 2020)
A specific, sensitive and accurate chiral technique has been developed for the quantification of elagolix enantiomer in a drug product. The present research work represents the development and validation of chromatographic technique for the separation of elagolix enantiomers on a chiral stationary phase (CSP) comprising a zwitterionic selector derived from cinchona alkaloid and sulfonic acid CHIRALPAK ZWIX (+) under isocratic condition containing 50mM Acetic acid and 25mM diethyl amine in water and methanol in the ratio of 02:98 v/v with 0.5 ml min-1 flow rate. Temperature of the column was monitored at 40°C with a resolving factor more than 3.2. The eluted compounds were monitored at 275 nm. The optimized method has high degree of selectivity with lower limiting values of detection and quantitation and were found to be 2.0 ng/ml and 7.5 ng/ml, respectively for the enantiomeric chiral impurity. The developed method was subjected for validation as per the ICH guidelines, produced good findings regarding specificity, accuracy, precision, robustness and linearity.